Disparity-driven vs blur-driven models of accommodation and convergence in binocular vision and intermittent strabismus - Horwood, Anna M. (J AAPOS, 2014)
PURPOSE: To propose an alternative and practical model to conceptualize clinical patterns of concomitant intermittent strabismus, heterophoria, and convergence and accommodation anomalies. METHODS: Despite identical ratios, there can be a disparity- or blur-biased “style” in three hypothetical scenarios: normal; high ratio of accommodative convergence to accommodation (AC/A) and low ratio of convergence accommodation to convergence (CA/C); low AC/A and high CA/C. We calculated disparity bias indices (DBI) to reflect these biases and provide early objective data from small illustrative clinical groups that fit these styles. RESULTS: Normal adults (n = 56) and children (n = 24) showed disparity bias (adult DBI 0.43 [95% CI, 0.50-0.36], child DBI 0.20 [95% CI, 0.31-0.07]; P = 0.001). Accommodative esotropia (n = 3) showed less disparity-bias (DBI 0.03). In the high AC/A–low CA/C scenario, early presbyopia (n = 22) showed mean DBI of 0.17 (95% CI, 0.28-0.06), compared to DBI of −0.31 in convergence excess esotropia (n=8). In the low AC/A–high CA/C scenario near exotropia (n = 17) showed mean DBI of 0.27. DBI ranged between 1.25 and −1.67. CONCLUSIONS: Establishing disparity or blur bias adds to AC/A and CA/C ratios to explain clinical patterns. Excessive bias or inflexibility in near-cue use increases risk of clinical problems.